Pendekatan Contextual Teaching and Learning dalam Pembelajaran Bahasa Indonesia di Kelas V SD Negeri 79 Palembang - Utami, Liza Tri; Idris, Muhamad; Prasrihamni, Mega (Jurnal Ilmiah Profesi Pendidikan, 2025)
This study aims to describe the Contextual Teaching and Learning (CTL) approach in learning Indonesian in grade V of SD Negeri 79 Palembang. The CTL approach is applied as an effort to overcome challenges in the learning process that is still conventional, where the role of educators is more dominant in delivering materials, while students are less actively involved. This study uses a descriptive qualitative method through data collection techniques in the form of observation, interviews, and documentation. The results of the study indicate that the CTL approach is able to increase the active involvement of students, foster interest in learning, and encourage critical thinking skills and writing skills. CTL provides space for students to relate learning materials to real-life contexts, so that the learning process becomes more meaningful and enjoyable. In addition, this approach strengthens positive interactions between students and optimizes the role of educators as facilitators in the teaching and learning process. In conclusion, the Contextual Teaching and Learning approach has been proven to have a positive impact on learning Indonesian in grade V. This approach is able to create a learning process that is more active, meaningful, and relevant to students' daily lives, thus supporting the improvement of critical thinking skills, interest in learning, and writing skills more optimally.